2006
DOI: 10.1021/jf0527798
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic Strategy for the Investigation of the Mode of Action of the Phytotoxin (5S,8R,13S,16R)-(−)-Pyrenophorol Using 1H Nuclear Magnetic Resonance Fingerprinting

Abstract: The biochemical mode of action of (5S,8R,13S,16R)-(-)-pyrenophorol isolated from a Drechslera avenae pathotype was investigated by using metabolic fingerprinting. (1)H NMR spectra of crude leaf extracts from untreated Avena sterilis seedlings and A. sterilis seedlings treated with pyrenophorol were compared with those obtained from treatments with the herbicides diuron, glyphosate, mesotrione, norflurazon, oxadiazon, and paraquat. Multivariate analysis was carried out to group treatments according to the mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 32 publications
1
15
0
1
Order By: Relevance
“…Central to these approaches is the application of a variety of robust analytical platforms such as, nuclear magnetic resonance spectroscopy (NMR) (Ratcliffe and Shachar-Hill 2001;Ott et al 2003;Ward et al 2003;Aliferis and Chrysayi-Tokousbalides 2006) and mass spectrometry (MS) (Fiehn et al 2000;Castrillo et al 2003;Smedsgaard and Nielsen 2004;Desbrosses et al 2005;Allwood et al 2008;Takahashi et al 2008). In spite of the importance of fungal metabolites, thorough assessment of their diverse metabolic landscape using metabolomic approaches is still in its infancy and has not been fully exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Central to these approaches is the application of a variety of robust analytical platforms such as, nuclear magnetic resonance spectroscopy (NMR) (Ratcliffe and Shachar-Hill 2001;Ott et al 2003;Ward et al 2003;Aliferis and Chrysayi-Tokousbalides 2006) and mass spectrometry (MS) (Fiehn et al 2000;Castrillo et al 2003;Smedsgaard and Nielsen 2004;Desbrosses et al 2005;Allwood et al 2008;Takahashi et al 2008). In spite of the importance of fungal metabolites, thorough assessment of their diverse metabolic landscape using metabolomic approaches is still in its infancy and has not been fully exploited.…”
Section: Introductionmentioning
confidence: 99%
“…41) However multivariate analysis (by PCA, PLS-DA and SIMCA) showed that although pyrenophorol treated samples were clearly differentiated from controls, they did not coclassify with any of the selected herbicide treatments.…”
Section: Chemical Treatments Environmental Influences and Pathogensmentioning
confidence: 93%
“…These details can be found in more extensive reviews dealing only with metabolomics (e.g., Aliferis and Chysayi-Tokousbalides, 2011). One approach to metabolomics is to generate one-dimensional (1D) proton NMR ( 1 H NMR) spectral fingerprints of crude extracts, hoping that the resulting information can provide clues to the mode of action, by comparing with fingerprints of phytotoxins with known modes of action (e.g., Ott et al, 2003; Aliferis and Chysayi-Tokousbalides, 2006). For obvious reasons, this method is inferior to actually identifying and quantifying each compound.…”
Section: Metabolomicsmentioning
confidence: 99%
“…This work was later expanded to 19 modes (Ott et al, 2003). The mode of action of the phytotoxin (5S,8R,13S,16R)-(1)-pyrenophorol was probed in Avena sterilis by using a 1 H-NMR fingerprinting of metabolites (Aliferis and Chysayi-Tokousbalides, 2006). The fingerprint did not correspond to those of the herbicides diuron, glyphosate, mesotrione, norflurazon, oxadiazon, or paraquat.…”
Section: Metabolomicsmentioning
confidence: 99%